The “appearing” and “disappearing” ascites in the treatment of colorectal cancer: a case report - Cui, Hong-Ming; Shu, Xin-Peng; Wei, Zheng-Qiang; Wu, Xing-Ye (Frontiers in Oncology, 2024)
Background Colorectal cancer (CRC) is one of the most common cancers worldwide. In the treatment of patients with CRC, oxaliplatin plays a pivotal role, with moderate side effects. Neurotoxicity, myelosuppression, ototoxicity, delayed hypersensitivity reactions, and rhabdomyolysis induced by oxaliplatin have been reported individually. However, the occurrence of oxaliplatin-induced ascites has not been reported previously. The objectives of this case report were to elaborate on the rare occurrence of ascites in a patient with CRC after oxaliplatin therapy and to explore its characteristics and causes. Case description We report on a case of upper rectal cancer seen in a 65-year-old man who underwent robotic-assisted laparoscopic anterior rectal resection. The patient developed ascites during postoperative adjuvant therapy with oxaliplatin and capecitabine. We ruled out tumor recurrence by laparoscopy, intraoperative biopsy, and biochemistry of the ascites. The patient did not experience a recurrence of ascites after discontinuation of chemotherapy. Conclusion This case suggests that chemotherapy with oxaliplatin might cause ascites. The mechanism of the oxaliplatin-induced liver injury was further discussed, which might have been the cause of ascite formation. When patients with CRC who underwent chemotherapy with oxaliplatin develop ascites, surgeons should actively determine whether this is a side effect of chemotherapy or is due to tumor recurrence in order to avoid unnecessary surgery.